52.5k views
4 votes
Help me answer this question please

Help me answer this question please-example-1
User DSCH
by
5.5k points

2 Answers

6 votes

Answer:

D.

Explanation:

User Webjockey
by
6.2k points
6 votes

For this case we have:

Let k> 0:

To graph
y = f (x) + k, the graph k units is moved up.

To graph
y = f (x) -k, the graph moves k units down.

Let h> 0:

To graph
y = f (x-h), the graph moves h units to the right.

To graph
y = f (x + h), the graph moves h units to the left.

So, we have:


y = f (x) = - \sqrt [3] {x}

Shifted 7 units up and 4 to the right means:


k = 1\\h = 4


y = f (x) = - \sqrt [3] {x-4} +7

Answer:

Option B

User Hyphen
by
6.5k points